Kohesivitas Kelompok Terhadap Semangat Kerja Pegawai Di Puskesmas Nanggalo Kota Padang - Satrifa Rifedi; Fitria Rahmi; Lala Septiyani Sembiring (Universitas Nusantara PGRI Kediri, 2021)
The purpose of this study is to see whether there is an influence of group cohesiveness on employees morale at the Nanggalo Padang Health Center. This study used a quantitative method by using a scale of psychological research instruments namely Group Cohesiveness Scale and Scale Morale. The sampling technique used saturated sampling technique by making all populations as samples. The results showed that Ha was accepted as evidenced by the measurement of a logistic regression analysis with a significance level (p) = 0,000 <0.05, it can be concluded that there was an influence of group cohesiveness on work morale of the employees at Nanggalo Padang Health Center.